Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5152/iao.2020.7598
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Surgical Outcome and Stage of Acquired Middle Ear Cholesteatoma: Revalidation of the EAONO/JOS Staging System

Abstract: The Journal of International Advanced Otology (J Int Adv Otol) is an international, peer reviewed, open access publication that is fully sponsored and owned by the European Academy of Otology and Neurotology and the Politzer Society. The journal is published triannually in April, August, and December and its publication language is English. The scope of the Journal is limited with otology, neurotology, audiology (excluding linguistics) and skull base medicine. The Journal of International Advanced Otology aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
4
1
5
Order By: Relevance
“…Early-stage cholesteatoma and pars flaccida cholesteatoma were determined to be independent predictors of hearing success in the multivariate analysis. This finding is consistent with that of a study conducted in 2020 by Ardic et al (2020) . The authors evaluated the surgical outcomes of cholesteatoma surgery and correlated them with the classifications of the newly proposed EAONO/JOS staging system.…”
Section: Discussionsupporting
confidence: 93%
“…Early-stage cholesteatoma and pars flaccida cholesteatoma were determined to be independent predictors of hearing success in the multivariate analysis. This finding is consistent with that of a study conducted in 2020 by Ardic et al (2020) . The authors evaluated the surgical outcomes of cholesteatoma surgery and correlated them with the classifications of the newly proposed EAONO/JOS staging system.…”
Section: Discussionsupporting
confidence: 93%
“…The authors showed that the recidivism rate was higher in children, in case of larger bone canal defect or cholesteatoma located in the supra-tubal recess; however, the prognostic role of the classification was defined as "uncertain" [13]. Ardıç et al [14] correlated the surgical outcomes with the EAONO/JOS staging system and reported no correlation between the staging system and the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…(2020 г. ), получены данные о большей частоте встречаемости пациентов с III стадией заболевания (31%), при этом доля пациентов с I и II стадиями составила соответственно 39 и 28%, с IV стадией -2% [8].…”
Section: новая классификация холестеатомы Eaono/josunclassified
“…Хирургическое лечение направлено на полное удаление патологического процесса с целью предотвращения развития осложнений и улучшения слуха. Ведущей проблемой хирургического лечения ХСУ является высокая частота рецидивирования, составляющая от 5 до 32% в зависимости от различных типов хирургического лечения [7,8].…”
unclassified
See 1 more Smart Citation